Linking Ecology and Physiology in Plant and Livestock Systems - Siti Nur Avira; Ainna Ummul Banin (Professorline, 2026)
Plants and livestock exist within complex ecological systems where their physiological processes are closely linked to environmental conditions. Understanding these interactions is essential for sustainable agriculture, food security, and environmental management. This paper examines the relationship between ecological factors and physiological mechanisms in plants and livestock, focusing on key processes such as photosynthesis, respiration, transpiration, metabolism, and reproduction. Using a literature-based review approach, this study synthesizes current scientific knowledge on plant and animal ecophysiology, highlighting how biotic and abiotic factors such as temperature, water availability, soil quality, and species interactions affect biological performance. The analysis shows that environmental stressors significantly influence productivity, survival, and adaptation in both plants and livestock. The findings emphasize the importance of integrating ecological and physiological perspectives to improve agricultural resilience under climate change. The paper concludes that better understanding of ecophysiological mechanisms can support more sustainable farming systems, optimize resource use, and enhance productivity while reducing environmental degradation.